2009
DOI: 10.1186/1741-7015-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the progression of pandemic influenza A (H1N1) in Vietnam and the opportunities for reassortment with other influenza viruses

Abstract: Background: A novel variant of influenza A (H1N1) is causing a pandemic and, although the illness is usually mild, there are concerns that its virulence could change through reassortment with other influenza viruses. This is of greater concern in parts of Southeast Asia, where the population density is high, influenza is less seasonal, human-animal contact is common and avian influenza is still endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…This 2-peak pandemic trend was observed in the other provinces as well [11]. The mean age of the confirmed cases in our study was 21.8 years and this was similar to other studies [3,5,6,[13][14][15][16]. In our study there was just 1 person aged > 65 years.…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫املجلد‬ ‫الثالsupporting
confidence: 79%
See 2 more Smart Citations
“…This 2-peak pandemic trend was observed in the other provinces as well [11]. The mean age of the confirmed cases in our study was 21.8 years and this was similar to other studies [3,5,6,[13][14][15][16]. In our study there was just 1 person aged > 65 years.…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫املجلد‬ ‫الثالsupporting
confidence: 79%
“…However, the frequency of symptoms varies widely in different countries [3,5,6,[13][14][15][16][17][18][19]. Different studies showed that most cases of infected H1N1 were mild, and severe cases of the disease were rare [4,5,8,20].…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫املجلد‬ ‫الثالmentioning
confidence: 99%
See 1 more Smart Citation
“…This yielded 21 articles eligible for the review (Fig. 2) [3,4,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. By reference checking and studying policy documents from the European Centre for Disease Prevention and Control (ECDC), the Centers of Disease Control and Prevention (CDC), and the World Health Organization (WHO), 15 additional articles or documents were found [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Methodsmentioning
confidence: 99%
“…10,11,14,16,22,30,31 The commonly used mathematical model among all is SIER model as it takes all factors of an epidemic phase of an individual i.e. Susceptible -Exposed -InfectiveRecovered.…”
Section: Totalmentioning
confidence: 99%